Parents’ approaches to numeracy support: what parents do is rarely what they think is most important - Msall, Camille; Douglas, Ashli-Ann; Rittle-Johnson, Bethany (Frontiers in Education, 2023)
The math children are exposed to at home is a crucial source of early math knowledge, but little is known about parents’ general approaches for supporting their children’s math development at home. The current study examined what general pedagogical approaches parents believed to be most important to use in their home and if these beliefs aligned with the approaches they reported using most often. In a survey of 344 U.S. preschool parents (56% mothers, 61% sons, 77% White, 79% with a bachelor’s degree or more), 83% of parents showed a mismatch in the pedagogical approach they used most often compared to what they believed to be most important to use. The most popular pedagogical approach to use was incorporating math during daily living experiences (the “daily living” approach) compared to three other approaches. Notably, although used most often, the “daily living” approach was the approach most frequently selected as least important. Rather, “direct teaching” was the approach most frequently selected as most important. Overall, this suggests a disconnect between how parents approach their home math support and what they believe is most important for their child’s math development at home.